A new agora: A project(ion) on the sub-centre - Salisbury Mills, Grace; Kebbell, Sam (Interstices: Journal of Architecture and Related Arts, 2016)
Supervisor: Sam Kebbell Carried out in the aftermath of the 2011 Christchurch Earthquake, this design-research project probes at architecture’s capacity to affect and embody an emergent polycentric urban condition: one ushered in by the effective elimination of the city’s CBD, overnight. The experimental design-research methodology deploys typology, contextuality, and self-consciously ‘urban’ programming to explore the socio-spatial and tectonic opportunities of polycentrism within the selected Christchurch suburb of Sumner (herein considered an emergent sub-centre). On the one hand, A New Agora is a radical and catalytic urban intervention, addressing the sub-centre as architecture’s project at a moment when Christchurch’s future was veiled in uncertainty. On the other, the project is a consideration and commentary on architecture’s multi-faceted, critical relationship with the city: ultimately arguing that the two must be treated as fundamentally intertwined, not least in the face of vast structural urban transformation.